The Effect Of Learning Through The Zoom Application On Students’ Learning Motivation In The Islamic Education Course - Ushwa Dwi Masrurah Arifin Bando; Nur Isra Ahmad (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
The rapid integration of digital technology in higher education has transformed learning practices, raising concerns about student motivation, particularly in value-based courses such as Islamic Religious Education (IRE). This study aims to examine the effect of learning through the Zoom application on students’ learning motivation and tests the hypothesis that synchronous online learning positively influences motivation. A quantitative explanatory survey design was employed involving 82 first-semester Management students at a university in Indonesia. Data were collected using a Likert-scale questionnaire measuring two variables: quality of Zoom-based learning (clarity of instruction, interaction, feature utilization, engagement, and learning comfort) and learning motivation (interest, attention, persistence, participation, and desire to understand). Purposive sampling was applied, and data were analyzed using descriptive statistics, normality and linearity tests, and simple linear regression. The results indicate that Zoom-based learning was perceived as good (M = 3.78), while student motivation was high (M = 3.91). Regression analysis revealed a positive and significant effect of Zoom-based learning on motivation (β = 0.628, p < 0.05), with a contribution of 43.5%. These findings suggest that synchronous interaction, social presence, and instructional clarity enhance student engagement and motivation. The study implies that optimizing interactive features and pedagogical strategies in synchronous online learning can support effective IRE instruction. In conclusion, Zoom-based learning is an effective medium for maintaining student motivation; future research is recommended to explore its impact on learning outcomes, religious attitudes, and the effectiveness of blended learning models.